2021
DOI: 10.1155/2021/6672978
|View full text |Cite|
|
Sign up to set email alerts
|

Salvianolic Acid B Protects Intervertebral Discs from Oxidative Stress‐Induced Degeneration via Activation of the JAK2/STAT3 Signaling Pathway

Abstract: Objective. To evaluate the influence of salvianolic acid B (SAB), an antioxidant derived from Danshen, on intervertebral disc degeneration (IDD) and its possible molecular mechanisms. Methods. Sixty adult rats were randomly grouped (control, IDD, and SAB IDD groups). IDD was induced using needle puncture. The rats received daily administration of SAB (20 mg/kg) in the SAB IDD group while the other two groups received only distilled water. The extent of IDD was evaluated using MRI after 3 and 6 weeks and histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…GSVA suggested that the gene sets highly correlated with IDD were associated with DNA repair, cell cycle, oxidative phosphorylation, IL-6-JAK-STAT3 signaling, and apoptosis. Among them, DNA repair and JAK-STAT3 signaling have been proved to be highly correlated with IDD ( Nasto et al, 2013 ; Dai et al, 2021 ). Mitochondria are the principal source of energy and ROS production in IVD cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSVA suggested that the gene sets highly correlated with IDD were associated with DNA repair, cell cycle, oxidative phosphorylation, IL-6-JAK-STAT3 signaling, and apoptosis. Among them, DNA repair and JAK-STAT3 signaling have been proved to be highly correlated with IDD ( Nasto et al, 2013 ; Dai et al, 2021 ). Mitochondria are the principal source of energy and ROS production in IVD cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al found that SAB slowed down the process of IDD and reconstructed the structure of IVD through in vivo experimental study. Subsequently, it was also confirmed that the levels of GSH and SOD2 in the degenerative IVD were reduced, and SAB treatment significantly reversed this change ( Dai S. et al, 2021 ). In additional in vitro experiments, SAB was found to reduce the levels of ROS and MDA and increase the levels of GSH and SOD2.…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 80%
“…Salvianolic acid is the most abundant polyphenolic of Salvia miltiorrhiza ; it exhibits anti-inflammatory, anticancer, antioxidant, and cardioprotective effects [ 78 ]. Dai et al [ 79 ] found that salvianolic acid B activated the JAK2/STAT3 signalling pathway, reduced ROS and MDA production, and upregulated GSH and SOD2 production to maintain mitochondrial function in NP cells. Transformation of the mesenchymal stem cells (MSCs) of IDD patients has attracted considerable attention.…”
Section: Natural Pharmacological Productsmentioning
confidence: 99%